ANALISIS POTENSI PENERIMAAN PAJAK HOTEL DAN PAJAK RESTORAN DI KABUPATEN LANDAK - Rosiska; Afif, Ali; Sartono; Fakhrul Yahya, Rizky (Jurnal Akuntansi, Auditing dan Investasi, 2023)
This study entitled "Analysis of Potential Hotel Tax and Restaurant Tax Revenues in Landak District". Regionalautonomy currently needs to be reviewed to find sources of regional income, Landak Regency has considerablepotential in tax revenues, especially hotel taxes and restaurant taxes. This research was conducted with the aimof knowing the magnitude of the potential for hotel tax and restaurant tax in 2021, the factors that are obstaclesto hotel tax and restaurant tax revenue and also to find out the efforts made by BPRD in overcoming obstacles tohotel tax and restaurant tax revenue. The method used in this research is descriptive method with a qualitativeapproach which is a writing that describes the actual situation based on the object under study, according to theactual situation at the time the research took place. The analytical tool used is potential analysis using thepotential calculation formula and questionnaire analysis. The results of the potential calculation show that thepotential for hotel taxes and restaurant taxes is very large for hotel taxes, namely Rp. 330,386,450. compared tothe realization that was received in 2021 it was relatively low, namely only Rp. 145,347,320. while for therestaurant tax Rp. 2,855,395,000. compared to the realization that was received in 2021 it was relatively low,namely only Rp. 2,507,541,762. factors constraining the lack of understanding of hotel and restaurant tax payersregarding tax payments and sanctions that are not fully applied to taxpayers. Efforts made by BPRD to overcometax revenue constraints by conducting outreach to hotel and restaurant tax payers.